Health and Safety Campaign at Palembang Zaadul Ma’ad Islamic Boarding School - Fitri Masito; I.G.A Ayu Mas Oka; Direstu Amalia; Yeti Komalasari; Eliya Eliya; Ririn Anggraini; Ninggarwati Ninggarwati; Eka Puspitasari Hutahuruk; Pebriliyana Pebriliyana; Adinda Safura; Dea Marta Melenia; Nabilah Hasna Arinda (Asosiasi Profesi Multimedia Indonesia, 2022)
The implementation of this socialization is to carry out the Tri dharma of Higher Education, namely carrying out “Pengabdian Kepada Masyarakat (PKM)” activities and compiling scientific journals. In addition, the purpose of this activity is to provide education to the Zaadul Ma'ad Islamic Boarding School regarding health and safety campaigns to improve the safety management system in the Islamic Boarding School environment. Matters related to the safety management system need to be socialized so that they can be applied in the environment so that unintentionally dangerous things can be avoided or handled quickly. The socialization method used was exposure by resource persons and discussions with students at the Zaadul Ma'ad Islamic boarding school in Palembang. The results obtained from this socialization are expected for the participants to understand the importance of a health and safety campaign in the environment around the airport to avoid risks. Then the results of the socialization were published on the Palembang Aviation Polytechnic social media and the PKM journal of the Palembang Aviation Polytechnic.